SOCIAL MEDIA ADDICTION, SELF-REGULATED LEARNING, AND ACADEMIC PROCRASTINATION: A MEDIATION ANALYSIS - Nurmaidah; Marsofiyati; Wolor, Christian Wiradendi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This study aims to examine the influence of social media addiction (X) on academic procrastination (Y) with self-regulated learning (Z) as a mediating variable among students of Public Vocational High School (SMKN) 1 Bogor. This research employed a quantitative approach using a survey method. The population consisted of 206 students in X and XI grade. The sample of 134 students was selected using the Isaac and Michael formula through proportional stratified random sampling. Data were analyzed using SmartPLS 4.1 with the Structural Equation Modeling–Partial Least Squares (SEM–PLS) technique, which includes analysis of the measurement model (outer model), structural model (inner model), and hypothesis testing. The results of the study indicate that (1) social media addiction positively influences academic procrastination, (2) social media addiction negatively influences self-regulated learning, (3) self-regulated learning negatively influences academic procrastination, and (4) there is an indirect effect of social media addiction on academic procrastination through self-regulated learning as a mediating variable.